Immunological significance of Mycobacterium leprae cell walls. - Melancon-Kaplan, J (1988)
Cell walls of Mycobacterium leprae, prepared by differential solvent extraction, were shown to contain arabinogalactan, mycolates, and peptidoglycan. In addition, amino acid analysis revealed the unexpected presence of large amounts of protein that retained potent immunological reactivity. Purified cell walls stimulated proliferation of T cells from tuberculoid, but not from lepromatous leprosy, patients and elicited delayed-type hypersensitivity skin reactions in guinea pigs and patients sensitized to M. leprae. Analysis of the precursor frequency of antigen-reactive human peripheral T cells revealed that as many cells (approximately equal to 1/6000) proliferate to antigen contained in cell walls as to intact M. leprae. Sequential removal of mycolates and arabinogalactan resulted in a large peptidoglycan-protein complex that retained all the immunological activity. This immunological reactivity and the inherent protein were destroyed by proteolysis. Thus, cell wall protein is a major contributor to cell-mediated immune reactivity to this pathogenic mycobacterium.